2009
DOI: 10.1111/j.1442-2042.2009.02296.x
|View full text |Cite
|
Sign up to set email alerts
|

Stage I seminoma: What should a practicing uro‐oncologist do in 2009?

Abstract: Testicular tumors are uncommon, but they continue to represent an important group of malignancies in young men. It is the most common solid malignancy in males between the ages of 20 and 35, and primary germ cell tumors are the most common histological type. In the United States in 2008, approximately 4800 cases of seminoma, approximately 4100 of which were stage I disease were projected after the completion of staging investigations.Remarkable progress has been made in the treatment of testicular seminoma ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
(159 reference statements)
0
7
0
Order By: Relevance
“…Recently, single‐agent carboplatin has been recognized as a potential option for the post‐orchiectomy management of stage I seminoma with encouraging short‐term results, 12,16,17 whereas long‐term results on cure rates and toxicities are yet to be clarified 18 . The surveillance policy was introduced in 1983 19 and has become an accepted option for the management of stage I seminoma, because subsequent prospective studies consistently showed that 80–85% of patients are cured by orchiectomy alone, and virtually all patients with relapse can be salvaged by subsequent chemotherapy, minimizing the burden of treatment 3,10 . The recent increase in choosing the surveillance policy in Japan might also be associated with our medical environment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, single‐agent carboplatin has been recognized as a potential option for the post‐orchiectomy management of stage I seminoma with encouraging short‐term results, 12,16,17 whereas long‐term results on cure rates and toxicities are yet to be clarified 18 . The surveillance policy was introduced in 1983 19 and has become an accepted option for the management of stage I seminoma, because subsequent prospective studies consistently showed that 80–85% of patients are cured by orchiectomy alone, and virtually all patients with relapse can be salvaged by subsequent chemotherapy, minimizing the burden of treatment 3,10 . The recent increase in choosing the surveillance policy in Japan might also be associated with our medical environment.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard , we sought to elucidate contemporary outcomes for Japanese patients with stage I seminoma treated with surveillance, adjuvant chemotherapy or adjuvant radio- Outcome of stage I seminoma in Japan therapy. Although the median follow up duration in the present study is relatively short, the results of RFS or the relapse pattern after each type of the post-orchiectomy management are equivalent to those found in previous studies, 1,3,[9][10][11][12] showing that the behavior of localized testicular seminoma is not different between Japanese and Western populations. If we can predict the patients at high risk of relapse, adjuvant therapies, such as chemotherapy or radiotherapy, could be applied to these selected patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the past 65 years, patients with stage I seminoma have been treated with adjuvant RT. [3] While we achieve 95-100% local control and survival rates this also brings along higher risks of early and late gonadal toxicities, secondary malignancy as well as highered risk of cardiovascular diseases. [4,5] As application of para-aortic field only (without pelvic field) [6,7] or delivering decreased RT doses at only about 20 Gy [8,9] aim to decrease specially the early toxicity; other modalities besides RT are in search to control the developing late risks.…”
Section: Introductionmentioning
confidence: 99%